(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
The study aims to shed light on the spread of the phenomenon of drug use and trafficking in Iraqi society in the recent period, and its impact on the Iraqi economy in general and on achieving the goals of sustainable development in Iraqi society. One of the most important effects of drug use and trafficking is the economic effects. A questionnaire was used on a random sample of young people in Babylon Governorate, and 300 questionnaire lists were distributed. The study concluded that the phenomenon of drug use and trafficking is a widespread phenomenon, and is a problem that threatens Iraqi society, especially the youth category, and there is a steady increase in the percentage of drug users and dealers. Drug use and trafficking greatly affects the achievement of economic development goals, which leads to an increase in the rate of poverty and unemployment in society. The study recommends working to impose strict control over drug smuggling and trafficking in local markets, and monitoring cafes, squares, and markets that constitute a center for drug use and trafficking.